Development of two driving cycles for utility vehicles. (December 2015) - Seers, P.; Nachin, G.; Glaus, M.
Highlights: 2 driving cycles are proposed for utility vehicles based on real driving conditions. Driving cycles show intensive driving very different than known driving cycles. Pollutant emissions and fuel consumption are reported for the proposed driving cycles. Comparison between the proposed driving cycle and the FTP-cycle is presented. Abstract: Driving cycles are used to assess vehicle fuel consumption and pollutant emissions. The premise in this article is that suburban road-work vehicles and airport vehicles operate under particular conditions that are not taken into account by conventional driving cycles. Thus, experimental data were acquired from two pickup trucks representing both vehicle fleets that were equipped with a data logger. Based on experimental data, the suburban road-work vehicle showed a mixed driving behavior of high and low speed with occasional long periods of idling. In the airport environment, however, the driving conditions were restricted to airport grounds but were characterized by many accelerations and few high speeds. Based on these measurements, microtrips were defined and two driving cycles proposed. Fuel consumption and pollutant emissions were then measured for both cycles and compared to the FTP-75 and HWFCT cycles, which revealed a major difference: at least a 31% increase in fuel consumption over FTP-75. This increased fuel consumption translates into higher pollutant emissions. When CO2 equivalent emissions are taken into account, the proposed cycles show an increase of at least 31% over FTP-75 and illustrate the importance of quantifying fleet speed patterns to assess CO2 equivalent emissions so that the fleet manager can determine potential gains in energy or increased pollutant emissions.